Species Diversity of Gastropoda in Seagrass Ecosystems at Mandalika Beach - Arif Safrillah; Karnan Karnan; Lalu Japa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Madak is looking for or hunting marine biota that can be consumed or has high economic value. Madak's activities can still threaten the existence of species on Mandalika Beach, one of which is Gastropods. This research focuses on the diversity of gastropod species that live in seagrass beds at Mandalika Beach. This study aims to identify the abundance and analyze the diversity index, uniformity index and dominance index of gastropod species in seagrass ecosystems on the Mandalika coast. This type of research is included in the type of descriptive-explorative research. This study describes the diversity of gastropod species in seagrass ecosystems on Mandalika Beach. The testing procedure utilized purposive examining. The research was conducted at 3 stations with 3 transects at each station. The results showed 27 species and 15 families of Gastropods. The species abundance value was 0.796 ind/m2, the species diversity index value was 1.849, the uniformity index value was 0.686, and the dominance index value was 0.280.